ANALYSIS OF THE STATE OF THE METALLURGICAL INDUSTRY OF UKRAINE IN THE CONDITIONS OF WAR - SMOLINSKA, Natalia; RAVOK, Solomiia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article considered main trends of Ukrainian metallurgical industry development in wartime conditions. It was established that the world leaders in the metallurgical industry are China, India, Japan, the USA, North Korea, Ukraine lost its global position from 14th to 25th place. Crude steel production volumes in Ukraine decreased by 70.7%. Despite the fact that the EU steel industry remains a highly energy-intensive industry, in Europe this sector is characterized by modern energy-saving equipment that is able to produce products with high added value for the global market based on innovative metadata. The influence of the metallurgical industry of Ukraine on the inflow of foreign investments into the state’s balance of payments was studied. Today, the metallurgical industry in Ukraine is inferior to the agricultural industry. The main problems faced by the metallurgical industry of Ukraine in the conditions of Russia’s armed aggression are the complicated sales of products due to the blockade of sea ports. The main threats faced by enterprises of the metallurgical industry are: destruction of their assets, which led to a complete stoppage or partial operation of enterprises; lack of working capital; logistical restrictions due to the blockade of ports (about 65% of the exports of the enterprises’ products were carried out by sea); shortage of energy resources (attacks on critical infrastructure facilities brought Ukraine’s energy system to the point of total frugality). The Ukrainian mining and metallurgical complex managed to remain at the level of 15-30% of capacity in 2022, primarily due to the support of Western partners, who provided their ports and lowered trade barriers. The main realistic scenario of support for metallurgical enterprises today remains the prolongation of reduced tariff rates for Ukrainian products and the inclusion of enterprises in the national post-war reconstruction program in the following years.